NIAT PEMBELIAN BARANG PADA GAME ONLINE MELALUI TEORI NILAI KONSUMSI DENGAN AMOS 21 - Pratiwi, Erni Dwi (Jurnal Pilar Nusa Mandiri, 2015)
Nowadays, online game is not just a game, it has become a commercial enterprise. A game tool transaction happens in it. the research is to analyze the factors which caused the players are interested in buying the items. The research uses the theory of Consumption Value, by Sheth, Newman, and Gross. there are six variables of analysis, such as Enjoyment Value, Character competency value, Visual authority value, Monetary value, Character identification dan Purchase intention. The results show that there are four variables which cause the players to buy the tools of the online game, they are Character competency value, Monetary value, Character identification, and Purchase Intention.